Kedudukan Harta sebagai Fitnah dalam QS. al-Humazah: Analisis Tematik atas Tafsir al-Sya’rāwī - Fakhry Fadhil; Ahmad Fathonih; Asep Mustofa Kamal (AT-TAISIR: Journal of Indonesian Tafsir Studies, 2025)
Wealth constitutes a fundamental aspect of human life, serving as a means of fulfilling needs and sustaining existence. However, the Qur’an emphasizes that wealth is not merely a blessing but also a fitnah (trial) that may lead to arrogance, pride, and behaviors characterized by humazah and lumazah, namely the tendency to mock, disparage, and demean others. Previous studies on Q.S. al-Humazah have predominantly adopted a normative ethical approach and have not sufficiently addressed contemporary phenomena such as exhibitionism, social-image construction, and symbolic superiority. This study aims to analyze the status and meaning of wealth in Q.S. al-Humazah through the perspective of Tafsīr al-Sya‘rāwī, in order to uncover the moral-psychological dimensions of wealth as a trial. Employing a library research method, this study uses Tafsīr al-Sya‘rāwī by Mutawallī al-Sya‘rāwī as its primary source and applies the al-adabī al-ijtimā‘ī (literary-social) exegetical approach, which emphasizes the relevance of Qur’anic values to social dynamics, moral conduct, and human behavior. The findings indicate that wealth in Q.S. al-Humazah is not confined to material possessions but also encompasses various forms of human advantages, such as intelligence, beauty, social status, success, and other forms of social prestige that may function as trials. When misused, these advantages foster a sense of superiority, encourage arrogance, and generate demeaning attitudes toward others. Theoretically, this study contributes to a broader understanding of wealth as a symbolic entity that shapes the quality of one’s faith, while methodologically affirming the relevance of the literary-social exegetical approach as a contextual model for interpreting the Qur’an in relation to contemporary social realities.